Recent advancements in bioremediation of metal contaminants - Dey, Satarupa, 1981-; Acharya, Biswa Ranjan (Advances in environmental engineering and green technologies (AEEGT) book series., 2021)
"This book explores bioremediation of pollutants from industrial wastes and examines the role of diverse forms of microbes in bioremediation of wastewater. Covering a broad range of topics including microorganism tolerance, phytoremediation, and fungi, the role of different extremophiles and biofilms in bioremediation are also discussed"--